New records of the solitary Vespidae (Hymenoptera: Vespidae: Masarinae and Eumeninae s. l.) from Central Asia, with new synonyms and description of a new species of Eumenes Latreille - Fateryga, Alexander V.; Proshchalykin, Maxim Yu. (Zootaxa, 2024)
A new species, Eumenes selisi Fateryga, sp. nov. is described from Uzbekistan. Three new synonymies are proposed: Masaris carli von Schulthess, 1922 = M. elegans Gusenleitner, 2002, syn. nov.; Parodontodynerus ephippium (Klug, 1817) = P. ephippium dalanicus Kurzenko, 1976, syn. nov.; Psiliglossa odyneroides (S.S. Saunders, 1850) = P. odyneroides kozhantshikovi Kostylev, 1940, syn. nov. Twenty-nine new country records are presented: two from Turkmenistan, four from Tajikistan, seven from Uzbekistan, seven from Kyrgyzstan, and nine from Kazakhstan. Masaris carli is excluded from the fauna of Iran and Psiliglossa odyneroides is excluded from the fauna of Russia. Observations on flower-visiting behavior of Chlorodynerus arenicola and Euodynerus setosus are reported.